DEVELOPMENT OF NARRATIVE ESSAY BASED ON DOCUMENTARY FILM HULA KETA AS TEACHING SUPPLEMENT TO FORM NATIONAL IDENTITY OF STUDENTS OF SMKN 3 MALANG - Nusantara, Galang Putra; Al Atok, A. Rosyid; Sukriono, Didik (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
Abstract This study addresses the challenge of disengagement in national identity education among vocational students by developing an innovative teaching supplement combining documentary film analysis and narrative essay writing. Centered on the documentary Hula Keta: Bukan Maluku Tanpa Sagu, which explores Tidore’s sago culinary traditions and communal values, the research bridges local cultural heritage with Pancasila principles to strengthen students' national identity. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the researchers created a coffee table book integrating film excerpts, reflective essays, and project-based activities aligned with Civics Education competencies. Material and media expert validation confirmed the product’s high feasibility, with 60% of indicators rated “highly feasible” and Cronbach’s Alpha reliability of 0.962. Implementation involving 36 culinary students at SMK Negeri 3 Malang revealed statistically significant learning outcome improvements, with mean scores rising from 51.67 (pre-test) to 89.31 (post-test) (*p* = 0.004). The intervention’s success stemmed from vocational contextualization, anchoring abstract concepts like environmental stewardship and national unity in relatable gastronomic heritage. Qualitative analysis of reflective essays demonstrated enhanced critical thinking, with students connecting Tidore’s gotong royong practices to broader civic responsibilities. By transforming passive learning into active cultural preservation through visual storytelling and place-based pedagogy, the narrative essay fostered pride in Indonesia’s diversity as a national asset. This research contributes to educational innovation by demonstrating how multimedia tools rooted in local wisdom can revitalize civic education, particularly in vocational settings where traditional didactic methods often fail. The findings emphasize the urgency of culturally responsive curricula in nurturing socially conscious citizens, offering a replicable model for integrating regional narratives into national identity frameworks across Indonesia’s multicultural landscape.